2020
DOI: 10.1504/ijpm.2020.10035979
|View full text |Cite
|
Sign up to set email alerts
|

Culture’s Consequences for Purchasing Comparing Purchasing Job Ad Requirements from Different European Countries with Cultural Models

Abstract: This research analyses the cultural differences in purchasing and supply management (PSM) job requirements from three European countries. The PSM job requirements in job advertisements have been compared with two cultural models: GLOBE and Hofstede. The universalism claim is tested based on comparing requirements in job advertisements for purchasers from Austria, Belgium, and the Netherlands. According to Hofstede, these three belong in different cultural clusters but just to one cultural area according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Interestingly, they found that carrying out (9) supplier relationship management, (10) innovation sourcing, ( 14) automation, and (15) technical skills requires multiple other competences, which were grouped in five factors, namely (1) networking skills, (2) result orientation, (3) imagination, (4) sellership skills, and (13) organisational insight and governance [11]. However, there is evidence that PSM job requirements are subject to cultural influence; in other cultural areas, nations, or regions, other requirements, mainly transferable, noncognitive, or soft skills, are demanded [38].…”
Section: Future Research and Managerial Implicationsmentioning
confidence: 99%
“…Interestingly, they found that carrying out (9) supplier relationship management, (10) innovation sourcing, ( 14) automation, and (15) technical skills requires multiple other competences, which were grouped in five factors, namely (1) networking skills, (2) result orientation, (3) imagination, (4) sellership skills, and (13) organisational insight and governance [11]. However, there is evidence that PSM job requirements are subject to cultural influence; in other cultural areas, nations, or regions, other requirements, mainly transferable, noncognitive, or soft skills, are demanded [38].…”
Section: Future Research and Managerial Implicationsmentioning
confidence: 99%
“…Berger, Kelly, Stek, & Zunk, 2018;Stek, Zunk, Berg, et al, 2018;Stinenbosch & Stek, 2017a; the requirements in PSM job advertisements (e.g. Chapter 4;Stek, 2016;Stek, Koch, Zunk, & Schiele, 2017;Stek, Zhang, Koch, Zunk, & Schiele, 2018;Stek, Zunk, Koch, & Schiele, 2021;Zunk & Stek, 2018); and performing studies on trends and future requirements for PSM (e.g. Bapeer, Stek, & Schiele, 2018;Bijl, Stek, & Sigurðardóttir, 2020;Hoorn & Stek, 2018;Kelly, Bals, Schulze, & Stek, 2020;Kelly, Vangorp, Stek, & Delke, 2020;Stek, 2017a;Stek, 2017bStek, , 2017cStek, , 2017dStek, , 2018aStek, , 2018bStek, Hoorn, & Schiele, 2019;Stek & Wieland, 2019;Stek, Wisniewski, van Dun, & Schiele, 2020;Tkáč, Kelly, & Stek, 2020).…”
Section: Figure 11 -Perfect Intellectual Outputs (Illustration By Project Perfect)mentioning
confidence: 99%
“…GLOBE model proposes nine cultural dimensions, including "Power Distance, Uncertainty Avoidance, Institutional Collectivism (Collectivism I), In-Group Collectivism (Collectivism II), Gender Egalitarianism, Assertiveness, Future Orientation, Performance Orientation, and Humane Orientation", to identify the practices that allow categorizing a society' s culture (society "is") and cultural values (society "should be") (Stek, 2022). Whereas Hofstede (1980) recognized six cultural aspects as the source of the first six dimensions.…”
Section: Culturementioning
confidence: 99%